Climate-smart agriculture and food security: Cross-country evidence from West Africa - Tabe-Ojong, Martin Paul Jr.; Aihounton, Ghislain B. D.; Lokossou, Jourdain C. (Elsevier, 2023)
In the face of climate change and extreme weather events which continue to have significant impacts on agricultural production, climate-smart agriculture (CSA) has emerged as one important entry point in reducing the emission of greenhouse gases and building climate resilience while ensuring increases in agricultural productivity with ensuing implications on food and nutrition security. We examine the relationship between CSA, land productivity (yields), and food security using a survey of farm households in Ghana, Mali, and Nigeria. To understand the correlates of the adoption of these CSA practices as well as the association between CSA, yields, and food security, we use switching regressions that account for multiple endogenous treatments. We find a positive association between the adoption of CSA practices and yields. This increase in yields translate to food security as we observe a positive association between CSA and food consumption scores. Although we show modest associations between the independent use of CSA practices such as adopting climate-smart groundnut varieties, cereal-groundnut intercropping, and the use of organic fertilizers, we find that bundling these practices may lead to greater yield and food security gains. Under the different combinations, the use of climate-smart groundnut varieties exhibit the strongest association with yields and food security. We also estimate actual-counterfactual relationships where we show that the adoption of CSA practices is not only beneficial to CSA adopters but could potentially be beneficial to non-CSA adopters should they adopt. These results have implications for reaching some of the sustainable development targets, especially the twin goals of increasing agricultural productivity and maintaining environmental sustainability.